Comportamiento agronómico de cuatro cultivares de zanahoria, mediante el sistema organopònico, en la zona de Babahoyo - Sandoya Fajardo, Alexandra Isabel (2015)
This research was conducted in the grounds of the Experimental Farm "San Pablo" of the Faculty of Agricultural Sciences at the Technical University of Babahoyo; located at km 7 ½ -Montalvo via Babahoyo, 7 m altitude, geographic coordinates 01 ° 47' 49'' south latitude and 79 ° 32' 00'' latitude West. Its climate is tropical humid with average temperatures of 25.2 ° C, annual rainfall of 1984.4 mm, with a light heliophany of 586.5 hours. The objective of this research was to evaluate the agronomic performance and yield four hybrid carrot seed under organopònico system, Babahoyo area. Seeds of hybrid carrot used: Nantes express, Miraflores f1, f1 and Chantenay royal Borec planted in hydroponics and using substrates common ground, farm land, cow dung and ashes. The treatments were four hybrids, for which purpose the experimental design "randomized complete block" with four treatments and four repetitions. Comparing the average it was performed with Tukey test at 95% probability........